The Importance of Digital Visual Learning Materials for Enhancing Middle School Students' Academic Performance in Islamic Subjects in the Sidikalang District - bancin, aisyah; Setiawan, Hasrian Rudi; Prasetia, Indra (Tarbawiyah Jurnal Ilmiah Pendidikan, 2024)
The purpose of this study is to characterize the importance of digital visual learning materials for raising student learning outcomes. The topic of discussion is Islamic religious education courses in the junior high schools in the Sidikalang District, namely SMPN 1 Sidikalang, SMPN 2 Sidikalang, and SMPN 3 Sidikalang, with a research background. This kind of research, which is being conducted from November 2023 to March 2024, is qualitative and uses a descriptive analytical study method. In order to gather factual information from schools, data was first collected through observation techniques. Later, data was collected through interview techniques and documentation studies. The study's findings demonstrate that representative photos, diagrams, and graphs are used in digital visual media for teaching the Islamic faith at three SMPN Sidikalang District locations, LCD or projector is used to operationalize the media. The steps involved in creating digital visual learning materials are needs analysis, planning, design, development, assessment, revision, implementation, long-term use, and ongoing evaluation. Digital visual learning materials have the potential to improve comprehension, jog memory, pique students' interest, and provide a contextual link between the content being taught and real-world experiences.